Learning Improvement in Youth Pledge Topic in Digital Era using Cooperative Learning Model - Sunarti Sunarti (Universitas Tanjungpura, 2022)
This study aims to increase knowledge and understanding of students in theyouth pledge learning which is considered forgotten by the globalization with theexistence of digitalization. It can be used to find out and understand youth programs tomaintain Indonesia as a complete and advanced country through the CooperativeLearning Model. The method with the research approach given to solve the problem inthis case provides a solution with quantitative descriptive. The Classroom ActionResearch (CAR) is a way of determining how to obtain data on these variables. In researchactivities, researchers follow an appropriate procedure by obtaining data, this is known asa data collection. The participants who joined this study were eighth grade students,totaling 33 students in SMPN 4 Sungai Raya. Based on the results of the research, 14students passed the test with a percentage of 42% during pre-cycle. In Cycle 1, there were29 students passed with a percentage of 87% and continued to Cycle II. There were 31students from 36 students with a percentage of 93% and 7% students have failed in CycleII. It can be conclude that Cooperative Learning Model can improve students’ ability tounderstand the concept. Thus, they are able to gain a broader knowledge.